Coercivity-enhanced iron nitride nanoparticles with high saturation magnetization
Patent Information
- Application Number
- JP2024192924
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-05-22
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-05-22
AI Technical Summary
は、飽和磁化の弱化を限定的にして、少なくとも180emu/g、好ましくは少なくとも195emu/gの飽和磁化を有する窒化鉄ナノ粒子を製造することである。
Smart Images

Figure 2025023983000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 851,190, filed May 22, 2019, the disclosure of which is incorporated herein by reference in its entirety.
[0002] The disclosed invention is in the field of iron nitride and magnetic materials made therefrom. [Background technology]
[0003] Iron nitride nanoparticles have been produced for many years by the controlled nitridation of iron and iron oxide nanoparticle precursors. These materials are of interest due to their potential to be processed into high performance non-rare earth containing permanent magnets. The α''-Fe 16 To date, no commercially viable iron nitride permanent magnets have been developed, because iron nitride nanoparticles with N2 phase have been found to have low saturation magnetization (MSat<180 emu / g). Therefore, to produce permanent magnets characterized by high coercivity (Hci>1000 Oe) and high saturation magnetization (MSat>180 emu / g), α''-Fe 16 There is a need to produce iron nitride nanoparticles having the N2 phase. Summary of the Invention
[0004] One problem that the present invention solves is that iron nitride nanoparticles with high coercivity (Hci>1000 Oe) are found to have low saturation magnetization (MSat<180 emu / g). Microscopic examination of the nanoparticles reveals that they are characterized by a core / shell structure with a non-ferromagnetic iron oxide shell. Without being bound by any theory of action, it is believed that the shell enhances the coercivity by magnetically isolating adjacent nanoparticles. However, the thickness of the shell is often found to be at least 5 nm. This thickness results in a significant weakening of the overall saturation magnetization of the core / shell nanoparticles. This weakening of the saturation magnetization substantially limits the performance of permanent magnets made from iron nitride nanoparticles.
[0005] Another problem that the present invention solves is that certain potentially advantageous nanoparticle shell materials, e.g., thin conformal materials of uniform thickness, are typically α''-Fe 16 The main problem is that the temperature required for the N2 phase is about 200°C higher than the maximum stable temperature for the α''-Fe 16 For structures consisting of a continuous shell around N2, these high-temperature materials are α''-Fe 16 After the N2 phase is formed in the core of the nanoparticles, it cannot be provided by the known deposition process, and if provided by the known deposition process, it is α''-Fe 16 The N2 phase decomposes. Low temperature deposition methods exist, such as electrolytic and electroless deposition, but they are very difficult to control and do not easily deposit thin materials on the nanoparticles. Examples of materials that require temperatures above 200°C for the formation of a shell layer by known deposition methods include nitrides, such as AlN, or ductile metals, such as Cu, Al, Sn, and Zn. These materials, along with α''-Fe 16 To allow for the combination of the N2 phase with the α''-Fe CrN phase, a novel structure is provided that offers additional advantages during the formation of the bulk magnet. 16Maximizing the saturation magnetization of compressed bulk magnets composed of N2 core-shell nanoparticles to produce commercially acceptable α''-Fe 16 To help prepare N2-based bulk magnets.
[0006] The present invention solves this problem by 1) limiting the shell thickness to 5 nm or less, preferably 4 nm or less, preferably 3.5 nm or less, preferably 3 nm or less, preferably 2.5 nm or less, even more preferably 2 nm or less, even more preferably 1 nm or less, and 2) requiring a minimum core diameter of at least 20 nm, preferably at least 30 nm, preferably at least 40 nm, even more preferably at least 50 nm (core diameters are typically less than 100 nm or less than 200 nm). As the core diameter increases and the shell thickness decreases, the overall saturation magnetization of the core / shell magnet increases. An advantage of the present invention is that it produces iron nitride nanoparticles with limited weakening of the saturation magnetization, with a saturation magnetization of at least 180 emu / g, preferably at least 195 emu / g.
[0007] Therefore, the present invention provides a method for producing a α''-Fe alloy comprising the steps of: 16 The present invention provides a plurality of iron nitride nanoparticles including an iron-based core including a N2 phase and a thin material deposited adjacent to the iron-based core, where the thin material is configured to enable nitridation of the iron-based core. Preferably, the iron nitride nanoparticles are monocrystalline α″-Fe with a non-magnetic shell. 16N2 core. This is because nanoparticles with multiple randomly oriented grains tend to be less magnetically aligned. Typically, suitable thin materials useful for making magnetic materials include non-ferromagnetic materials. Non-limiting examples of suitable non-ferromagnetic thin materials include FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn, or any combination thereof. Often, the thin material is provided as a continuous thin shell on the core, but the thin material may be a discontinuous shell, such as a discontinuous shell having irregularities, perforations, holes, or both, on the core nanoparticle. The thin material covering the core may be suitably configured to be a substantially continuous shell through which nitrogen can diffuse. Exemplary iron nitride nanoparticles are characterized by having an MSat of greater than about 145 emu / g and a coercivity of greater than about 1000 Oe.
[0008] In many embodiments, the nanoparticles are characterized by X-ray diffraction using an X-ray source having a Cu target configured to emit single wavelength Cu-Kα X-rays, which gives rise to a diffraction peak (at a 2θ of about 42.7°) of α″-Fe 16 The ratio of the integrated intensity of the α-Fe(211) peak (at a 2θ of about 82.2°) to the N2(202) peak is less than or equal to 0.2, preferably less than or equal to 0.15, or even less than or equal to 0.10.
[0009] Furthermore, the present invention provides a magnetic material having a magnetic powder having a magnetic material weight of 50% or more of α''-Fe 16 A magnetic material is provided that includes a plurality of iron nitride nanophases, characterized by including a N2 phase, and a non-ferromagnetic material disposed between the nanophases. Preferably, the non-ferromagnetic material disposed between the nanophases includes FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn, or any combination thereof. Exemplary magnetic materials are characterized by having an MSat of greater than 160 emu / g and a coercivity of greater than about 700 Oe.
[0010] In certain embodiments, the present invention provides core / shell iron nitride nanoparticles having a non-ferromagnetic shell, some of which is 1-2 nm thick.
[0011] In another embodiment, the present invention provides iron nitride nanoparticles characterized by having a coercivity greater than about 2000 Oe and a saturation magnetization greater than about 195 emu / g.
[0012] In certain embodiments, the present invention provides a 1-2 nm thick non-ferromagnetic shell on the iron nitride core.
[0013] In another embodiment, the present invention uses low temperature passivation to form a 1-2 nm thick non-ferromagnetic shell on the iron nitride core.
[0014] In some embodiments, the present invention uses amorphous iron oxide nanoparticles as precursors.
[0015] In another embodiment, the present invention provides a nanoparticle structure having a predominantly α-Fe core and discontinuous shell layers.
[0016] In some embodiments, the present invention provides a method for producing a substantially α″-Fe 16 The present invention provides iron nitride nanoparticles having an N2 core and a discontinuous shell layer.
[0017] In certain embodiments, the shell is provided before the nitride phase, the shell being discontinuous and not coating the entire area of the core, and then converted, for example by nitridation, to a primarily α″-Fe 16 The Fe core is nitrided, consisting of the α-Fe phase resulting in a core of N2, which is surrounded by a discontinuous shell.
[0018] In another embodiment, the present invention provides a method for producing a α″-Fe nitridable nanotube with a continuous shell made of a material that allows for nitridation of the Fe core. 16The present invention provides nanoparticles characterized in that they have a structure having a core of N2, for example due to the inherent properties of the shell material or because the shell is thin, for example less than 3 nm thick.
[0019] In a particular embodiment, the present invention provides core / shell iron nitride nanoparticles, where a continuous shell is provided prior to the nitridation of the phase, which allows the nitridation of the Fe core despite the presence of the shell, and then, for example, by nitridation, to form mainly α″-Fe 16 The Fe core is nitrided, consisting of the α-Fe phase resulting in a core of N2, said core being surrounded by a discontinuous shell.
[0020] In another embodiment, the present invention provides a nanotube nanotube comprising a nanotube nanotube having a first discontinuous shell and a second thin continuous or discontinuous shell layer having a thickness of less than 3 nm, the nanotube nanotube being composed primarily of α″-Fe 16 The present invention provides nanoparticles having a structure with a N2 core.
[0021] In some embodiments, a first shell is provided prior to the nitride phase to provide core / shell iron nitride nanoparticles in which the shell is discontinuous and does not coat the entire area of the core. This is then converted, for example by nitridation, to a primarily α″-Fe 16 The Fe core is nitrided, consisting of α-Fe phase resulting in a core of N2, the core being surrounded by a discontinuous shell. A second shell is then provided, the second shell being mainly composed of α''-Fe 16 The N2 core and the first shell material are coated either continuously or discontinuously.
[0022] The general description and the following detailed description are exemplary or explanatory only and are not restrictive of the invention, as defined in the appended claims. Other aspects of the invention will become apparent to those skilled in the art from the detailed description of the invention provided herein.
[0023] The summary, as well as the following detailed description, will be better understood when read in conjunction with the accompanying drawings. For the purpose of illustrating the invention, there are shown in the drawings exemplary embodiments of the invention; however, the invention is not limited to the specific methods, components and apparatus disclosed. Additionally, the drawings are not necessarily drawn to scale. [Brief description of the drawings]
[0024] [Figure 1-1] 1 provides a hysteresis loop for aluminum oxide coated iron nitride nanoparticles produced in Example 1. [Figure 1-2] 1 provides an X-ray diffraction pattern of the aluminum oxide coated iron nitride nanoparticles produced in Example 1. [Figure 1-3] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 1. [Figure 1-4] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 1. [Figure 1-5] 1 shows an elemental map of aluminum localized at the surface of aluminum oxide coated iron nitride nanoparticles according to Example 1. [Figure 1-6] 1 shows an elemental map of iron distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 1. [Figure 1-7] 1 shows an elemental map of nitrogen distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 1. [Figure 1-8] 1 provides images of aluminum oxide coated iron nitride nanoparticles from which elemental maps of Al, Fe and N were obtained in Example 1. [Figure 1-9] 1 provides the hysteresis loop of an isotropic compressed magnet made by uniaxially compressing the aluminum oxide coated iron nitride nanoparticles produced in Example 1 to a pressure of 10 MPa. [Figure 1-10]1 provides the hysteresis loop of an isotropic compressed magnet made by uniaxially compressing the aluminum oxide coated iron nitride nanoparticles produced in Example 1 to a pressure of 12 MPa. [Figure 2-1] 1 provides a hysteresis loop for aluminum oxide coated iron nitride nanoparticles produced in Example 2. [Figure 2-2] 1 provides an X-ray diffraction pattern of the aluminum oxide coated iron nitride nanoparticles produced in Example 2. [Figure 2-3] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 2. [Figure 2-4] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 2. [Figure 2-5] 1 provides an elemental map of aluminum localized at the surface of aluminum oxide coated iron nitride nanoparticles according to Example 2. [Figure 2-6] 1 provides an elemental map of iron distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 2. [Figure 2-7] 1 provides an elemental map of nitrogen distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 2. [Figure 2-8] 1 provides a TEM image of aluminum oxide coated iron nitride nanoparticles from which elemental maps of Al, Fe and N were obtained in Example 2. [Figure 2-9] 1 provides the hysteresis loop of an isotropic compressed magnet made by uniaxially compressing the aluminum oxide coated iron nitride nanoparticles produced in Example 2 to a pressure of 10 MPa. [Figure 2-10] 1 provides the hysteresis loop of an isotropic compressed magnet made by uniaxially compressing the aluminum oxide coated iron nitride nanoparticles produced in Example 2 to a pressure of 12 MPa. [Figure 3-1]1 is a hysteresis loop of aluminum oxide coated iron nitride nanoparticles produced in Example 3. [Figure 3-2] 1 provides an X-ray diffraction pattern of the aluminum oxide coated iron nitride nanoparticles produced in Example 3. [Figure 3-3] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 3. [Diagram 3-4] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 3. [Figure 3-5] 1 provides an elemental map of aluminum localized at the surface of aluminum oxide coated iron nitride nanoparticles according to Example 3. [Diagram 3-6] 13 provides an elemental map of iron distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 3. [Diagram 3-7] 13 provides an elemental map of nitrogen distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 3. [Diagram 3-8] 1 provides a transmission electron microscope image of aluminum oxide coated iron nitride nanoparticles from which elemental maps of Al, Fe and N were obtained in Example 3. [Figure 4-1] 1 provides the hysteresis loop of aluminum oxide coated iron nitride nanoparticles produced in Example 4. [Figure 4-2] 1 provides the hysteresis loop of aluminum oxide coated iron nitride nanoparticles produced in Example 4. [Figure 4-3] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 4. [Figure 4-4] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 4. [Figure 4-5]1 provides an elemental map of aluminum localized at the surface of aluminum oxide coated iron nitride nanoparticles according to Example 4. [Figure 4-6] 1 provides an elemental map of iron distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 4. [Figure 4-7] 1 provides an elemental map of nitrogen distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 4. [Figure 4-8] 1 provides a transmission electron microscope image of aluminum oxide coated iron nitride nanoparticles from which elemental maps of Al, Fe and N were obtained in Example 4. [Figure 5-1] 1 provides the hysteresis loop of aluminum oxide coated iron nitride nanoparticles produced in Example 5. [Figure 5-2] 1 provides an X-ray diffraction pattern of the aluminum oxide coated iron nitride nanoparticles produced in Example 5. [Figure 5-3] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 5. [Figure 5-4] 1 provides a transmission electron microscope image measuring the thickness of the aluminum oxide coating on the iron nitride nanoparticles produced in Example 5. [Figure 5-5] 1 provides an elemental map of aluminum localized at the surface of aluminum oxide coated iron nitride nanoparticles according to Example 5. [Figure 5-6] 13 provides an elemental map of iron distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 5. [Figure 5-7] 13 provides an elemental map of nitrogen distributed throughout the mass of aluminum oxide coated iron nitride nanoparticles according to Example 5. [Figure 5-8] 1 provides a TEM image of aluminum oxide coated iron nitride nanoparticles from which elemental maps of Al, Fe and N were obtained in Example 5. [Figure 5-9]13 provides the hysteresis loop of an isotropic compressed magnet made by uniaxially compressing the aluminum oxide coated iron nitride nanoparticles produced in Example 5 to a pressure of 10 MPa. [Figure 5-10] 13 provides the hysteresis loop of an isotropic compressed magnet made by uniaxially compressing the aluminum oxide coated iron nitride nanoparticles produced in Example 5 to a pressure of 12 MPa. [Figure 6] We show the configuration of close packing for a random packing of 10,000 polydisperse spheres at density φ=0.662. The distribution of sphere radii is log-normal with a standard deviation of σ=0.3. [Courtesy of Baranau and Tallarek, "Random-close packing limits for monodisperse and polydisperse hard spheres," Soft Matter., Vol.10, 2014, pp.3826-41] [Figure 7-A] 1 shows a contour plot of the saturation magnetization (Bsat) of a bulk iron nitride magnet including bonded iron nitride nanoparticles made according to the present invention, illustrating how the saturation magnetization (Bsat) varies with nanoparticle core diameter d (nm) and thickness t (nm) for a nanoparticle core Bsat of 225 emu / gram and a volume filling factor of 63%. [Figure 7-B] 1 shows a contour plot of saturation magnetization (Bsat) of a bulk iron nitride magnet including bonded iron nitride nanoparticles made according to the present invention, illustrating how the saturation magnetization (Bsat) varies with nanoparticle core diameter d (nm) and thickness t (nm) for a nanoparticle core Bsat of 250 emu / gram and a volume filling factor of 63%. [Figure 8] 1 is an alignment of the characteristics of two exemplary iron nitride core / shell nanoparticles (Case 1 and Case 2) made according to the present invention. [Figure 9] 1 is a list of features of an exemplary magnet composed of iron nitride core / shell nanoparticles made according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The present invention may be better understood by reference to the following detailed description in conjunction with the accompanying drawings and examples that form a part of this disclosure. It is understood that the present invention is not limited to the specific apparatus, methods, applications, conditions or parameters described and / or illustrated herein, and that the terminology used herein is for the purpose of describing particular embodiments by way of example only, and is not intended to limit the claimed invention. Furthermore, unless the context clearly dictates otherwise, as used herein, including the appended claims, the singular forms "a," "an," and "the" include the plural, and reference to a particular numerical value includes at least that particular value. As used herein, the term "plural" means more than one. When a range of values is expressed, certain other embodiments include from one particular value and / or to the other particular value. Similarly, when a value is expressed as an approximation, by use of the preceding "about," it is understood that the particular value forms certain other embodiments. All ranges are inclusive and combinable.
[0026] Certain features of the invention that are, for clarity, described herein in the context of individual embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention that are, for brevity, described in the context of a single embodiment, may also be provided separately or in any subcombination of the individual. Further, references to values recited in ranges include each and every value within that range.
[0027] The present invention allows the formation of core / shell iron nitride nanoparticles. The core is made of α″-Fe with a mass fraction of at least 50%, preferably at least 80%. 16 The remaining mass fraction of the core may be composed of α-Fe, α'-FeN, γ'-FeN, and ε-Fe 2-3 It may consist of a mixture of N phases.
[0028] The thin material for the shell may be composed of one or more non-ferromagnetic materials or phases in the shell. Non-limiting examples of non-ferromagnetic materials include FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, AlN, MnN, Cu, Al, Sn, and Zn.
[0029] The diameter of the core may be 20-200 nm, preferably 20-100 nm, even more preferably 40-80 nm. The thickness of the shell may be 0.1-4.0 nm, preferably 0.1-1.0 nm. The shell material may be less than 4 nm, less than 3.5 nm, less than 3 nm, less than 2.5 nm, less than 2 nm, or less than 1.5 nm.
[0030] The shape of the core / shell nanoparticles may be spherical or non-spherical. Examples of non-spherical shapes include rods, needles, prolate spheroids, oblate spheroids, disks and plates. Further examples of non-spherical shapes include porous structures such as foams, gels and sponges.
[0031] The cores can be produced by a method that includes nitridation of nanoparticle precursors. The nanoparticle precursors may include α-Fe, Fe3O4, α-Fe2O3 and γ-Fe2O3. The nanoparticle precursors may include amorphous nanoparticles composed of iron, iron oxide, iron nitride, iron boride and mixtures thereof. If iron oxide nanoparticle precursors are used, the nanoparticles may undergo a reduction treatment prior to nitridation. When α-Fe nanoparticle precursors are used, the nanoparticles may be directly nitrided. If the α-Fe nanoparticle precursor has a pre-existing oxide shell, the α-Fe nanoparticle precursor may undergo a reduction treatment prior to nitridation. The α-Fe nanoparticle precursor may undergo an oxidation treatment prior to the reduction and nitridation treatment.
[0032] The non-ferromagnetic shell can be formed on the core using any type of suitable chemical deposition technique. Another approach to forming the shell is to expose the iron nitride core to an atmosphere with a controlled oxidizing potential. Yet another approach to forming the shell is to precipitate the shell on the surface by chemical and / or electrochemical reaction.
[0033] Atomic layer deposition (ALD) is a versatile technique for producing thin, conformal coatings on a wide variety of surfaces and substrates. Originally, ALD was developed as an alternative to other methods such as chemical vapor deposition (CVD) and physical vapor deposition (PVD) for the manufacture of semiconductor devices. The principle of operation is the sequential adsorption of reactant compounds onto the exposed substrate surface. The adsorption reaction is self-limiting and stops when a uniform surface layer completely coats the substrate. The introduction of the next reactant in the sequence 1) reacts with the first reactant layer to form a uniform layer of the first atoms in the compound being coated, thus forming a new substrate surface, and 2) adsorbs a new layer composed of the next reactant layer. In this manner, thin films with precisely controlled composition and thickness can be grown one atomic layer at a time. A wide variety of exemplary ALD reactants for forming a wide variety of compositions suitable for use as thin materials disposed adjacent to iron nitride nanoparticle cores are provided in the table below.
[0034] Table of ALD reactants suitable for producing thin materials located adjacent to iron nitride nanoparticle cores. [Table 1-1] [Table 1-2] [Table 1-3] [Table 1-4] [Table 1-5] [Table 1-6] [Table 1-7] [Table 1-8] [Table 1-9] [Table 1-10]
[0035] Individual powders and particles can also be used as substrates in ALD coating processes. The use of a fluidized bed reactor allows for intimate mixing of the powders with the vaporized ALD reactants. Mechanical agitation, such as the use of vibrators attached to the reactor, can aid in fluidizing the particles. In this configuration, the fluidized bed reactor is filled with a batch of powder fluidized in a column that causes the gas to flow vertically. The ALD reactants are introduced into the reactor sequentially, and a purge step is used to remove excess reactants when changing from one ALD reactant to the next in the sequence. The reactor can be contained within a furnace that can heat the fluidized bed to the reaction temperature required for ALD.
[0036] Using a fluidized bed reactor, the surface of the magnetic iron nanoparticles can be coated with a coating of aluminum oxide. The purpose of the aluminum oxide coating is to passivate the surface of the iron nanoparticles and inhibit the oxidation of the iron nanoparticles when they are exposed to air. Suitable ALD reactants include trimethylaluminum (TMA) and water (H2O). In the aluminum oxide coating, TMA is the aluminum source and H2O is the oxygen source. A suitable ALD reaction temperature can be at least 180°C, and multiple cycles of the TMA+H2O ALD process can be used to form an Al2O3 shell on the iron nanoparticle core. Ideally, the thickness of the aluminum oxide shell is less than 5 nm.
[0037] A fluidized bed reactor can also be used to convert iron oxide nanoparticles to iron nitride nanoparticles. The fluidized bed reactor can be configured to flow both H2 and NH3 gases through a fluidized bed of nanoparticles at elevated temperature. A suitable reactor can first reduce the iron oxide nanoparticles to iron using a flow of H2 at a temperature of 350°C to 500°C. Then, in the same reaction vessel, the iron nanoparticles can be transformed to iron nitride nanoparticles using a flow of NH3 at a temperature of 110°C to 180°C. The iron nitride nanoparticles can then be cooled to room temperature and passivated by briefly flowing a mixture of N2 and air through the nanoparticles. The passivation process results in a layer of iron oxide on the surface of the nanoparticles that inhibits further oxidation. A suitable process can produce iron nitride nanoparticles with saturation magnetization of greater than 200 emu / g and coercivity as high as 1000 Oe.
[0038] Forming a thin shell of material by exposing the iron nitride core to an atmosphere with a controlled oxidation potential can be accomplished by flowing a gaseous mixture of oxygen and an inert gas over the iron nitride core. The exposure can occur immediately after nitridation. The inert gas used in the mixture can include helium, argon, nitrogen or mixtures thereof. The volume fraction of oxygen in the mixture can be 20% or less, preferably 5% or less. The thickness of the shell can be limited by using high gas flow rates and low gas temperatures to carry away the heat of reaction.
[0039] The nitriding and / or shelling can be carried out in a stationary or rotating reactor, which may be a tube, double cone or another shape that facilitates the reaction. The nitriding and / or shelling can also be carried out in a fluidized bed reactor.
[0040] The reaction vessel may be vibrated intermittently or continuously during the nitridation and / or shell formation process. Vibration may improve mixing during the process.
[0041] A limitation of nanoparticle processing is their tendency to form agglomerates. In general, nanoparticle agglomerates reduce yields by preventing surface-mediated reactions from going to completion. In the case of permanent magnets, agglomerates reduce performance by preventing the production of magnetically anisotropic magnets.
[0042] Certain processes in nitridation and / or shell formation may benefit from control of the size, size distribution and / or bulk density of the agglomerates, for example, operation of a fluidized bed reactor may only be practical if the agglomerates are in a range of sizes and bulk densities that allow for fluidization.
[0043] Methods to deagglomerate and / or control the agglomeration of nanoparticles include shear mixing, low energy milling and ultrasonic treatment, which can be used before, during or after nitridation and / or shell formation.
[0044] It is further recognized that the properties of the final permanent magnet may depend on the size distribution of the nanoparticle precursors, and for this reason it may be necessary to modify the size distribution of the nanoparticles before, during or after the nitridation and / or shell formation steps.
[0045] Methods for controlling the size distribution of nanoparticles include filtration, sieving and mechanical grinding. Filtration methods include magnetic separation, electrostatic separation and centrifugation in a cyclone. Sieving methods include the use of screens and selectively and non-selectively permeable membranes. Mechanical grinding methods include sonication, high energy ball milling and jet milling.
[0046] In one other embodiment, the present invention specifically provides a method for producing a α″-Fe 16 The present invention relates to a structure including nanoparticles having a partial, incomplete or discontinuous shell surrounding a core of α''-Fe2O3 and an associated method for making the structure. Hereinafter, this type of nanoparticle shell layer is defined as a discontinuous shell. A discontinuous shell means that there is a portion of the surface of the core particle that is not covered by the shell material. By having a discontinuous shell, the nitridation process can occur after the shell is formed. This eliminates the limitation on the temperature used in forming the shell, thereby allowing the production of α''-Fe2O3 with improved magnetic properties. 16 A novel set of starting materials for producing bulk magnets containing the N2 phase is provided.
[0047] In one other embodiment, the present invention is specifically a structure including nanoparticles having a substantially continuous shell layer composed of a material that is thin enough to allow nitridation of Fe through it or to allow nitridation of Fe to proceed despite the presence of the material, and related methods for making the structure. The shell material, the thickness of the shell material, or both the shell thickness and the shell material provide a means to allow nitridation after the shell material is provided. The shell thickness requirement may depend on the material, but may be on the order of 1-3 atomic layers, or 3 nm or less, or thicker. Examples of materials that allow nitridation of Fe despite its presence include shell materials that have pinholes or porosity, or shell materials that essentially allow diffusion of nitrogen (N) through their thin solid shell. The diffusing species may be N atoms, N2 molecules, NH3 molecules, or some intermediate form, such as (NH4) + ions. Additionally, diffusion can occur as a gas throughout the volume of the shell, along the surface of the pinholes, or through the pinholes / discontinuities if the pinholes are large enough. More generally, the thin material forming the shell layer is configured such that mass transport of the nitrogen-containing species via mechanisms can include volume and / or surface diffusion. The advantages are similar to the discontinuous shell structure, in that the nitridation process can occur after the shell is formed, again removing the temperature limitation imposed by the temperature used in forming the shell.
[0048] In one other embodiment, the present invention provides a method for producing a .alpha.''-Fe. 16 The structure includes a N2 core, a discontinuous first shell material, and a thin (less than 3 nm) continuous second shell material to create the structure. The second thin continuous shell material allows for processing of the nanopowder with some exposure to an oxygen-containing environment during the manufacturing process, which can simplify the manufacturing process. However, this second shell may have a negative effect on the saturation magnetization of the bulk, fully densified final magnet.
[0049] A further advantage of any of these embodiments is realized during densification and compression of the nanoparticles into a bulk magnet. For example, during the bulk magnet formation process using steps such as high shear deformation, where the shell structure of the nanoparticles is composed of a ductile metal, e.g., Cu, Al, Sn, or Zn, the shell regions of the ductile metal in the individual nanoparticles can be compressed and bonded, resulting in the formation of α-′′Fe in the core region of the nanoparticle in the densified material. 16 A continuous or nearly continuous shell structure is formed around the N2 phase. Without being bound by theory of operation, the continuous or nearly continuous shell formed by subsequent compression is composed of a minimal amount of non-magnetic material and can reduce or even eliminate the volume of the bulk magnet composed of binder, thereby maximizing the saturation magnetization of the material. Additionally, the bound shell regions provide magnetic separation that allows for single domain or single domain-like coercivity mechanisms. Alternatively, if less discontinuous shell material is used in the pre-densified nanoparticle structure, then domain wall pinning coercivity mechanisms can be exerted following compression, along with higher saturation magnetization.
[0050] The various embodiments described provide a means to nitride the iron core of the nanoparticles after the formation of the shell (continuous or discontinuous), removing the limitation on the processing temperature for the formation of the shell structure. This allows the formation of either continuous or discontinuous shell structures composed of one or more materials that could not be used before. The methods described herein allow for materials such as certain oxides such as Al2O3, nitrides such as AlN, ductile metals such as Cu, Al, Sn and Zn, combinations of these materials, or other materials with properties that further enhance the properties of the nanoparticles and / or the compressed bulk magnet material. EXAMPLES
[0051] Example 1 The starting material for Example 1 was iron nitride nanoparticles prepared by reduction and nitridation of commercially sourced γ-Fe2O3 nanoparticles in a 2-inch diameter rotary tube furnace. A total of nine lots of nanoparticles, each lot approximately 1.2 grams in mass, were combined together to make the starting material for the aluminum oxide coating operation. First, the γ-Fe2O3 nanoparticles were transformed into α-Fe nanoparticles by reduction in H2 gas flow at 200 sccm (standard cubic centimeters per minute) at 335°C for 12 hours. The α-Fe nanoparticles were then transformed into iron nitride nanoparticles by flowing NH3 gas at a flow rate of 60 sccm at 135°C for 22 hours. The iron nitride nanoparticles were removed and stored in a nitrogen-filled glove box. Phase analysis by X-ray diffraction showed that the iron nitride nanoparticles were α''-Fe 16 N2 and ε-Fe 2-3 The phase fraction was mostly α''-Fe. 16 It was N2.
[0052] The aluminum oxide coating was deposited by atomic layer deposition (ALD) in a fluidized bed reactor. The fluidized bed reactor was loaded with 10 grams of iron nitride nanoparticles in a nitrogen (N2) filled glove box. The reactor was heated to 100°C to fluidize the nanoparticle bed in a flow of N2 carrier gas. The aluminum oxide coating was deposited, one atomic layer at a time, by alternately introducing vaporized trimethylaluminum (TMA) and water in the N2 carrier gas for a total of nine cycles. Each cycle was started by flowing TMA until the methane signal in the residual gas analyzer faded and the trimethylaluminum signal increased sharply (indicating that all surfaces in the reactor were coated with aluminum). Before flowing H2O, the reactor was purged by flowing N2. H2O was flowed until the H2O signal increased sharply (indicating that all surfaces in the reactor were coated with aluminum oxide). Before starting the next cycle, the reactor was purged again by flowing N2.
[0053] The resulting aluminum oxide coated iron nitride nanoparticles were removed in air and their magnetic properties and microstructure were characterized. Figure 1-1 shows the hysteresis loop of the coated nanoparticles. The intrinsic coercivity was measured to be 2008 Oe and the saturation magnetization was measured to be 191 emu / gram. Figure 1-2 shows that the coated nanoparticles still retain the α''-Fe 16 N2 phase and ε-Fe 2-3 The X-ray diffraction pattern shows a mixture of N and α-Fe phases. The major X-ray diffraction peaks of each phase present in Example 1 are identified below in Table 1. Quantitative phase analysis by Mössbauer spectroscopy shows that the α-Fe 16 This shows that the mass fraction of the N2 phase is 74%. Table 1: X-ray diffraction peaks of each phase present in Example 1 [Table 2]
[0054] High-resolution transmission electron microscopy was performed to measure the thickness of the aluminum oxide coating on the surface of the iron nitride nanoparticles. Figures 1-3 and 1-4 show the presence of a uniform coating on the nanoparticles, with a thickness of 1.6-2.5 nm. Energy dispersive X-ray analysis was used to obtain elemental maps. Figure 1-5 is an elemental map showing that the aluminum signal is located on the surface of the nanoparticles. Figures 1-6 and 1-7 show that the Fe and N signals, respectively, are located in the core of the iron nitride nanoparticles. Figure 1-8 is an image of the coated nanoparticles from which the elemental maps were obtained.
[0055] Isotropic magnets were made from aluminum oxide coated iron nitride nanoparticles by uniaxial compression. The nanoparticles were loaded into a 0.25 inch diameter cylindrical die and compressed in a hydraulic press. Figure 1-9 is a hysteresis loop of a magnet compressed to a pressure of 10 MPa. The magnet has a saturation magnetization of 180 emu / gram and an intrinsic coercivity of 1712 Oe. Figure 1-10 is a hysteresis loop of a magnet compressed to a pressure of 12 MPa. The magnet has a saturation magnetization of 181 emu / gram and an intrinsic coercivity of 1674 Oe.
[0056] Example 2 The starting material for Example 2 was a total of 9 lots of iron nitride nanoparticles, each lot approximately 1.2 grams in mass, prepared in a rotary tube furnace by the same method described in Example 1. The atomic layer deposition parameters in Example 2 were the same as those in Example 1, except for the fluidized bed temperature, which was set at 130°C. The hysteresis loop measured on the coated nanoparticles (Figure 2-1) shows a saturation magnetization of 181 emu / gram and an intrinsic coercivity of 1916 Oe. Again, the X-ray diffraction pattern (Figure 2-2) shows α''-Fe 16 N2 phase and ε-Fe 2-3 The main X-ray diffraction peaks for each phase present in Example 2 are identified below in Table 2. Mössbauer spectroscopy shows a mixture of α-Fe 16 The mass fraction of the N2 phase is 67%. The thickness of the aluminum oxide was measured to be 2.0-4.0 nm by high-resolution transmission electron microscopy (Fig. 2-3 and Fig. 2-4). Elemental maps (Fig. 2-5, Fig. 2-6, Fig. 2-7 and Fig. 2-8) show Al on the surface and Fe and N in the core of the coated iron nitride nanoparticles. Table 2: X-ray diffraction peaks of each phase present in Example 2 [Table 3]
[0057] Figure 2-9 is the hysteresis loop of a 0.25 inch diameter isotropic magnet compressed uniaxially to a pressure of 10 MPa. This magnet has a saturation magnetization of 183 emu / gram and an intrinsic coercivity of 1617 Oe. Figure 2-10 is the hysteresis loop of a magnet compressed to a pressure of 12 MPa. This magnet has a saturation magnetization of 180 emu / gram and an intrinsic coercivity of 1566 Oe.
[0058] Example 3 The starting material for Example 3 was commercially sourced γ-Fe2O3 nanoparticles. Prior to loading into the fluidized bed reactor, the γ-Fe2O3 nanoparticles were sieved to obtain a sieve fraction of 25 μm to 53 μm. After loading into the fluidized bed reactor, the γ-Fe2O3 nanoparticles were transformed into α-Fe nanoparticles by reduction in H2 gas flow at 200 sccm at 315 °C for 15 hours. The α-Fe nanoparticles were then transformed into iron nitride nanoparticles by flowing NH3 gas at 120 sccm at 135 °C for 40 hours. A coating of aluminum oxide was applied to the surface of the iron nitride nanoparticles by atomic layer deposition using 9 cycles of alternating introduction of trimethylaluminum and water at 100 °C.
[0059] The hysteresis loop for the coated nanoparticles (Figure 3-1) shows a saturation magnetization of 158 emu / gram and an intrinsic coercivity of 1798 Oe. The X-ray diffraction pattern (Figure 3-2) shows that the α''-Fe 16 N2 phase and ε-Fe 2-3 The results show the desired mixture of N and α-Fe phases, with the presence of iron oxide indicating that the γ-Fe2O3 nanoparticles did not completely transform to α-Fe prior to nitridation. The major X-ray diffraction peaks for each phase present in Example 3, except for the iron oxide phase, are identified below in Table 3. The thickness of the aluminum oxide was measured to be 1.9-3.6 nm by high resolution transmission electron microscopy (Figures 3-3 and 3-4). Elemental maps (Figures 3-5, 3-6, 3-7 and 3-8) show Al on the surface and Fe and N in the core of the coated iron nitride nanoparticles. Table 3: X-ray diffraction peaks of each phase present in Example 3 [Table 4]
[0060] Example 4 The starting material for Example 4 was commercially sourced γ-Fe2O3 nanoparticles. The γ-Fe2O3 nanoparticles are supplied as a dry, agglomerated powder. The agglomerates of γ-Fe2O3 nanoparticles have a typical size distribution of 1-500 μm. Prior to loading into the fluidized bed reactor, the γ-Fe2O3 nanoparticles were sieved to obtain a sieve fraction of 25 μm-53 μm. After loading into the fluidized bed reactor, the γ-Fe2O3 nanoparticles were transformed into α-Fe nanoparticles by reduction in H2 gas flow at 200 sccm at 315 °C for 24 hours. The α-Fe nanoparticles were then transformed into iron nitride nanoparticles by NH3 gas flow at 120 sccm at 130 °C for 60 hours. A coating of aluminum oxide was applied to the surface of the iron nitride nanoparticles by atomic layer deposition using 9 cycles of alternating introduction of trimethylaluminum and water at 100 °C.
[0061] The hysteresis loop for the coated nanoparticles (Figure 4-2) shows a saturation magnetization of 151 emu / gram and an intrinsic coercivity of 1756 Oe. The X-ray diffraction pattern (Figure 4-2) shows that the α''-Fe 16 N2 phase and ε-Fe 2-3 The X-ray diffraction pattern shows the desired mixture of α-Fe and α-N phases. No peaks corresponding to iron oxide were observed in the X-ray diffraction pattern. The major X-ray diffraction peaks of each phase present in Example 4 are identified below in Table 4. The thickness of the aluminum oxide was measured to be 1.6-3.2 nm by high resolution transmission electron microscopy (Figures 4-3 and 4-4). Elemental maps (Figures 4-5, 4-6, 4-7 and 4-8) show Al on the surface and Fe and N in the core of the coated iron nitride nanoparticles. Table 4: X-ray diffraction peaks of each phase present in Example 4 [Table 5]
[0062] Example 5 The starting material for Example 5 was iron nitride nanoparticles prepared by reduction and nitridation of commercially sourced γ-Fe2O3 nanoparticles in a 2-inch diameter rotary tube furnace. A total of 27 lots of nanoparticles, each lot approximately 0.3 grams in mass, were combined together to make the starting material for the aluminum oxide coating operation. First, the γ-Fe2O3 nanoparticles were transformed to α-Fe nanoparticles by reduction in H2 gas flow at 100 sccm at 330 °C for 5 hours. The α-Fe nanoparticles were then transformed to iron nitride nanoparticles by flowing NH3 gas at a flow rate of 60 °C at 135 °C for 22 hours. The iron nitride nanoparticles were removed and stored in a nitrogen-filled glove box. Phase analysis by X-ray diffraction showed that the iron nitride nanoparticles were α''-Fe 16 N2 and ε-Fe 2-3 The phase fraction was mostly α''-Fe. 16 It was N2.
[0063] A fluidized bed reactor was loaded with 10 grams of iron nitride nanoparticles in a N2-filled glove box. A coating of aluminum oxide was applied to the surface of the iron nitride nanoparticles by atomic layer deposition using 9 cycles of alternating trimethylaluminum and water at 200° C. The coated nanoparticles were removed in air and characterized.
[0064] The hysteresis loop for the coated nanoparticles (Figure 5-1) shows a saturation magnetization of 143 emu / gram and an intrinsic coercivity of 787 Oe. The X-ray diffraction pattern (Figure 5-2) shows that the iron nitride nanoparticles are α''-Fe 16 N2 and ε-Fe 2-3The phase fraction was predominantly α-Fe. The major X-ray diffraction peaks for each phase present in Example 5 are identified below in Table 5. Quantitative phase analysis by Mössbauer method showed that the α-Fe 16 The mass fraction of the N2 phase is 18%. These analyses show that the process temperature of 200 °C results in a α''-Fe 16 The N2 phase is decomposed to give α-Fe and ε-Fe 2-3 N. 16 The decomposition of the N2 phase to α-Fe is believed to cause the decrease in intrinsic coercivity of Example 5 relative to the other examples. Table 5: X-ray diffraction peaks of each phase present in Example 5 [Table 6]
[0065] By high-resolution transmission electron microscopy (Figs. 5-3 and 5-4), the thickness of the aluminum oxide coating was measured to be 3.0-5.0 nm. The elemental map (Fig. 5-5) shows that Al is located on the surface of the nanoparticles. Furthermore, the elemental maps (Figs. 5-6 and 5-7) show that Fe and N are sequestered in the core of the nanoparticles, and more specifically, α''-Fe 16 Evidence of decomposition of the N2 phase is shown. Figures 5-8 are images of the coated nanoparticles from which elemental maps were obtained.
[0066] Figure 5-9 is the hysteresis loop of a 0.25 inch diameter isotropic magnet compressed uniaxially to a pressure of 10 MPa. This magnet has a saturation magnetization of 150 emu / gram and an intrinsic coercivity of 681 Oe. Figure 5-10 is the hysteresis loop of a magnet compressed to a pressure of 12 MPa. This magnet has a saturation magnetization of 148 emu / gram and an intrinsic coercivity of 677 Oe. The coercivity of the magnet is due to the increase in the α''-Fe 16 The coercivity of the magnets produced in Examples 1 and 2 is smaller due to the decomposition of the N2 phase.
[0067] Considering these results, nanoparticles suitably provided herein are characterized as having an X-ray diffraction pattern substantially similar to that shown in Figures 1-2, 2-2, or 3-2. In addition, the intensity ratio of X-ray diffraction peaks can be used as a "fingerprint" of acceptable phase fractions of nanoparticles provided herein. For example, the α-Fe(211) peak (at about 82.2° 2θ) / α''-Fe(211) peak (at about 42.7° 2θ) 16 The ratio of integrated intensities of the N2(202) peaks is desirably 0.20 or less, more preferably 0.15 or less. The X-ray diffraction patterns and diffraction angles provided herein were measured using an X-ray source having a Cu target configured to emit single wavelength Cu-Kα X-rays.
[0068] α''-Fe for each nanoparticle 16 The grain size (core thickness) of the N2 phase is calculated by the α''-Fe 16 The core thicknesses were calculated using the Scherrer equation applied to the X-ray diffraction peak widths of N2. The peak parameters were determined using the Rietveld refinement method calibrated for the instrumental broadening of the diffractometer. The core thicknesses are listed in Table 6.
[0069] A summary of the properties and characteristics of the aluminum oxide coated iron nitride nanoparticles made according to the examples is provided below in Table 6. Table 6: Properties of aluminum oxide coated iron nitride nanoparticles [Table 7]
[0070] A summary of the magnetic properties of isotropic magnets produced by uniaxial compression of aluminum oxide coated iron nitride nanoparticles is provided below in Table 7. Table 7: Magnetic properties of isotropic magnets [Table 8]
[0071] A summary of the quantitative analysis of the mass fractions of the layers present in Examples 1, 2 and 5, as determined by the Mössbauer method, is provided below in Table 8. Table 8: Mass fractions of phases determined by Mössbauer method [Table 9]
[0072] When ranges are used herein for physical properties, such as molecular weight, or chemical properties, such as chemical formula, all combinations and subcombinations of the ranges for specific embodiments therein are intended to be included.
[0073] The disclosures of each patent, patent application and publication cited or described in this application are hereby incorporated by reference in their entirety.
[0074] Those skilled in the art will recognize that many changes and modifications can be made to the preferred embodiments of the present invention and that such changes and modifications can be made without departing from the spirit of the present invention. It is therefore intended that the appended claims cover all such equivalent variations that are within the true spirit and scope of the present invention.
[0075] Item 1. 50% or more by weight of α''-Fe 16 1. A plurality of iron nitride nanoparticles comprising: an iron-based core including an N2 phase; and a thin material disposed adjacent to the iron-based core, the thin material configured to enable nitridation of the iron-based core.
[0076] Item 2. The plurality of iron nitride nanoparticles described in item 1, wherein the thin material comprises a non-ferromagnetic material.
[0077] Item 3. The plurality of iron nitride nanoparticles of item 2, wherein the non-ferromagnetic material comprises FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn, or any combination thereof.
[0078] Item 4. A plurality of iron nitride nanoparticles according to item 1, wherein the thin material is configured as a discontinuous shell.
[0079] Item 5. A plurality of iron nitride nanoparticles as described in item 1, wherein the thin material is configured as a substantially continuous shell through which nitrogen can diffuse.
[0080] Item 6. A plurality of iron nitride nanoparticles according to item 1, characterized in that they have an Msat of greater than about 145 emu / g and a coercivity of greater than about 1000 Oe.
[0081] Item 7. The α''-Fe nanoparticles 16 2. The iron nitride nanoparticles of claim 1, wherein the mass fraction of N2 phase is characterized by the Mössbauer method as being greater than 60%.
[0082] Item 8. A plurality of nanoparticles comprising an iron nitride core and a thin non-ferromagnetic material disposed adjacent to said core, said nanoparticles having at least 50% α''-Fe by weight. 16 A plurality of nanoparticles comprising an N2 phase.
[0083] Item 9. The plurality of nanoparticles of item 8, wherein the non-ferromagnetic thin material has an average thickness of less than 5 nm.
[0084] Item 10. A plurality of nanoparticles according to item 8, characterized in that they have an Msat of greater than about 145 emu / g and a coercivity of greater than about 1000 Oe.
[0085] Item 11. When characterized by X-ray diffraction using an X-ray source having a Cu target configured to emit single wavelength Cu-Kα X-rays, the X-ray diffraction shows an α-Fe(211) peak (at 2θ of 82.2°) / α''-Fe(211) peak (at 2θ of 42.7°). 16 A plurality of nanoparticles giving rise to diffraction peaks in which the ratio of integrated intensities of the N2(202) peak is 0.2 or less.
[0086] Item 12. 50% or more α''-Fe by weight of magnetic material 16 1. A magnetic material comprising: a plurality of iron nitride nanophases, characterized by comprising an N2 phase; and a non-ferromagnetic material disposed between said nanophases.
[0087] Item 13. The magnetic material of item 12, wherein the non-ferromagnetic material disposed between the nanophases comprises FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn, or any combination thereof.
[0088] Item 14. The magnetic material of item 12, characterized in that it has an Msat of greater than about 160 emu / g and a coercivity of greater than about 700 Oe.
[0089] Item 15. The magnetic material of item 12, wherein the thickness of the non-ferromagnetic material disposed between the nanophases has an average thickness of less than 5 nm.
[0090] Item 16. 50% or more by weight of α''-Fe 16 1. A plurality of iron nitride nanoparticles comprising: an iron-based core comprising an N2 phase; and a shell on the iron-based core comprising a material characterized as being a ductile metal, a non-ferromagnetic material, or both.
[0091] Item 17. The iron nitride nanoparticles of item 16, wherein the core has a major dimension of between 20 nm and 200 nm.
[0092] Item 18. The iron nitride nanoparticles of item 16, wherein the core has a major dimension of between 40 nm and 80 nm.
[0093] Item 19. The iron nitride nanoparticles according to item 16, wherein the shell has a thickness of 0.1 nm to 5 nm.
[0094] Item 20. The iron nitride nanoparticles according to item 16, wherein the shell has a thickness of 0.1 nm to 4 nm.
[0095] Item 21. The iron nitride nanoparticles according to item 16, wherein the shell has a thickness of 0.1 nm to 3 nm.
[0096] Item 22. The iron nitride nanoparticles according to item 16, wherein the nanoparticles are spherical.
[0097] 23. The iron nitride nanoparticles of claim 16, wherein the nanoparticles are non-spherical.
[0098] 24. The iron nitride nanoparticles according to claim 16, wherein the nanoparticles have a porous structure.
[0099] Item 25. The iron nitride nanoparticles of item 16, wherein the nanoparticles are in the form of rods, needles, prolate spheroids, oblate spheroids, discs and plates, foams, gels, or sponges.
[0100] Item 26. The core is selected from the group consisting of α-Fe, α'-Fe8N, γ'-Fe4N and ε-Fe 2-3 17. The iron nitride nanoparticles according to item 16, further comprising one or more phases of N.
[0101] 27. The iron nitride nanoparticles of claim 16, wherein the shell further comprises FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, MnN, or any combination thereof.
[0102] 28. The iron nitride nanoparticles according to claim 16, wherein the ductile metal comprises Cu, Al, Sn, Zn, or any combination thereof.
[0103] Item 29. A bulk magnet comprising a plurality of iron nitride nanoparticles according to any one of the preceding items.
[0104] Item 30. The bulk magnet described in item 29, wherein the saturation magnetization value (Msat) of the bulk magnet is 180 emu / g or more.
[0105] Item 31. The bulk magnet described in item 29, wherein the saturation magnetization value (Msat) of the bulk magnet is 195 emu / g or more.
[0106] Item 32. The bulk magnet described in item 29, wherein the bulk has a coercive force value (Hci) of 1500 Oe or more.
[0107] reference Ahvenniemi, E. et al., “Review Article: Recommended reading list of early publications on atomic layer deposition-Outcome of the “Virtual Project on the History of ALD”,” Journal of Vacuum Science & Technology A: Vacuum,Surfaces,and Films, Vol.35, 2016, 010801 King, DM et al., "Atomic layer deposition on particles using a fluidized bed reactor with in situ mass spectrometry", Surface & Coatings Technology, Vol. 201, 2007, pp 9163-71 LFHakim, LF et al., “Synthesis of oxidation-resident metal nanoparticles via atomic layer deposition”, Nanotechnology, Vol. 18, (2007), 354093 Sankar et al., "Iron nitride powders for use in magnetic, electromagnetic, and microelectronic devices," U.S. Patent No. 8,535,634, September 17, 2013 The present invention can be embodied in the following manner. (Appendix 1) a. 50% or more α''-Fe by weight 16 with an iron-based core containing N2 phase; b. a thin material disposed adjacent to the iron-based core, the thin material configured to enable nitridation of the iron-based core; A plurality of iron nitride nanoparticles comprising: (Appendix 2) 2. The plurality of iron nitride nanoparticles of claim 1, wherein the thin material comprises a non-ferromagnetic material. (Appendix 3) 3. The plurality of iron nitride nanoparticles of claim 2, wherein the non-ferromagnetic material comprises FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn, or any combination thereof. (Appendix 4) 2. The plurality of iron nitride nanoparticles of claim 1, having an Msat greater than about 145 emu / g and a coercivity greater than about 1000 Oe. (Appendix 5) A plurality of nanoparticles comprising an iron nitride core and a thin non-ferromagnetic material disposed adjacent to the core, the nanoparticles comprising at least 50% α″-Fe by weight. 16 A plurality of nanoparticles comprising an N2 phase. (Appendix 6) 6. The plurality of nanoparticles of claim 5, wherein the average thickness of the non-ferromagnetic thin material is less than 5 nm. (Appendix 7) 6. The nanoparticles of claim 5, having an Msat greater than about 145 emu / g and a coercivity greater than about 1000 Oe. (Appendix 8) When characterized by X-ray diffraction using an X-ray source having a Cu target configured to emit single wavelength Cu-Kα X-rays, the X-ray diffraction shows an α-Fe(211) peak (at a 2θ of about 82.2°) / α''-Fe(211) peak (at a 2θ of about 42.7°). 16 A plurality of nanoparticles giving rise to diffraction peaks in which the ratio of integrated intensities of the N2(202) peak is 0.2 or less. (Appendix 9) a. 50% or more α''-Fe based on the weight of the magnetic material 16 A plurality of iron nitride nanophases, characterized in that they include an N2 phase; b. a non-ferromagnetic material disposed between the nanophases; 4. A magnetic material comprising: (Appendix 10) 10. The magnetic material of claim 9, wherein the non-ferromagnetic material disposed between the nanophases comprises FeO, α-Fe2O3, ZnO, Al2O3, SiO2, TiO2, ZrO2, CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn, or any combination thereof. (Appendix 11) More than 50% by weight of α''-Fe 16 with an iron-based core containing N2 phase; a shell on said iron-based core comprising a material characterized as a ductile metal, a non-ferromagnetic material, or both; A plurality of iron nitride nanoparticles comprising: (Appendix 12) 12. The iron nitride nanoparticles of claim 11, wherein the core has a major dimension between 20 nm and 200 nm. (Appendix 13) 12. The iron nitride nanoparticles according to claim 11, wherein the shell has a thickness of 0.1 nm to 5 nm. (Appendix 14) 12. The iron nitride nanoparticles of claim 11, wherein the ductile metal comprises Cu, Al, Sn, Zn, or any combination thereof. (Appendix 15) A bulk magnet comprising a plurality of iron nitride nanoparticles according to any one of claims 1 to 14. (Appendix 16) The saturation magnetization value of the bulk magnet (Msat 16. The bulk magnet described in claim 15, wherein the molecular weight distribution (Mg / cm2) is 180 emu / g or more. (Appendix 17) The coercive force value of the bulk magnet (H ci 16. The bulk magnet of claim 15, wherein the magnet strength is 1500 Oe or more.
Claims
1. a. 50% or more by weight of α''-Fe 16 N 2 an iron-based core containing a phase; b. a thin material disposed adjacent to the iron-based core, the thin material configured to enable nitridation of the iron-based core; and the thin material is Al 2 O 3 wherein the thin material has an average thickness of 0.1-1.0 nm and has an Msat greater than 195 emu / g and a coercivity greater than 2000 Oe.
2. The plurality of iron nitride nanoparticles of claim 1 , wherein the thin material comprises a non-ferromagnetic material.
3. The non-ferromagnetic material is FeO, α-Fe 2 O 3 , ZnO, Al 2 O 3 , SiO 2 , TiO 2 , ZrO 2 3. The plurality of iron nitride nanoparticles of claim 2, comprising: CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn, or any combination thereof.
4. A plurality of nanoparticles comprising an iron nitride core and a thin non-ferromagnetic material disposed adjacent to the core, the nanoparticles having at least 50% α″-Fe by weight. 16 N 2 phase, and the non-ferromagnetic thin material is 2 O 3 wherein the non-ferromagnetic thin material has an average thickness of 0.1-1.0 nm and has an Msat greater than 195 emu / g and a coercivity greater than 2000 Oe.
5. 5. The nanoparticles of claim 4, having an Msat greater than 145 emu / g and a coercivity greater than 1000 Oe.
6. When characterized by X-ray diffraction using an X-ray source having a Cu target configured to emit single wavelength Cu-Kα X-rays, the X-ray diffraction shows an α-Fe(211) peak (at 2θ of 82.2°) / α″-Fe(211) peak (at 2θ of 42.7°). 16 N 2 2. The nanoparticles of claim 1, which give rise to a diffraction peak having a ratio of integrated intensities of the (202) peaks of 0.2 or less.
7. a. α''-Fe: 50% or more by weight of the magnetic material 16 N 2 a plurality of iron nitride nanophases, b. a non-ferromagnetic material disposed between said nanophases; and the non-ferromagnetic material is Al 2 O 3 wherein the non-ferromagnetic material has an average thickness of 0.1-1.0 nm and has an Msat greater than 195 emu / g and a coercivity greater than 2000 Oe.
8. The non-ferromagnetic material disposed between the nanophases is FeO, α-Fe 2 O 3 , ZnO, Al 2 O 3 , SiO 2 , TiO 2 , ZrO 2 10. The magnetic material of claim 9, comprising: CoO, NiO, Mn, Cr, CrN, MnN, Cu, Al, Sn, Zn or any combination thereof.
9. 50% or more by weight of α''-Fe 16 N 2 an iron-based core containing a phase; a shell on said iron-based core comprising a material characterized as a ductile metal, a non-ferromagnetic material, or both; The shell is made of Al. 2 O 3 wherein the shell has an average thickness of 0.1-1.0 nm, and has an Msat greater than 195 emu / g and a coercivity greater than 2000 Oe.
10. 10. The iron nitride nanoparticles of claim 9, wherein the longest dimension of the core is between 20 nm and 200 nm.
11. 10. The iron nitride nanoparticles of claim 9, wherein the ductile metal comprises Cu, Al, Sn, Zn, or any combination thereof.
12. A bulk magnet comprising a plurality of nanoparticles according to any one of claims 1 to 11.
Citation Information
Patent Citations
Ferromagnetic granular powder and method for manufacturing the same, as well as anisotropic magnet, bonded magnet, and pressed-powder magnet
JP2012149326A
Method for manufacturing ferromagnetic iron nitride particle powder, anisotropic magnet, bonded magnet, and compressed-powder magnet
JP2013080922A
Iron nitride magnet
JP2017228656A
Method for producing magnetic particles, magnetic particles, and magnetic body
WO2014122993A1